SCIENCE & TECHNOLOGY IN KERALA: EMBARKING ON A NEW S&T STRATEGY - State Planning Board, Government of Kerala
The S&T support system in Kerala appears a little lopsided and too general to make any substantive impact. There are no focused programmes to support innovations. Most programmes focus on supporting science and technology. Kerala faces the economic, social and environmental challenges. The KPP 2030 proposes a sustainable innovation strategy that will help steer the Kerala economy out of the economic, social and environmental challenges that the state it faces. The mission of this policy will be to mobilise S&T to Kerala’s advantage, towards building a more competitive and sustainable knowledge economy with the help of science and technology. This new, focused policy will create a platform that encourages the private sector to compete with the world on the basis of their innovative products, services, and technologies.